P-038 Predictors of ventriculostomy infection in a large cohort. (22nd July 2019) - Sweid, A; Tjoumakaris, S; Wamsley, C; Mann, E; Neely, C; Head, J; Gooch, M; Herial, N; Alexander, T; Missios, S; Chalouhi, N; Rosenwasser, R; et al.
Abstract : Background: External ventricular drain (EVD) placement is a common neurosurgical procedure. While this procedure is simple and effective, infection is a major limiting factor. Factors predictive of infection reported in the literature are not conclusive. Objective: The aim of this retrospective single-center large sample was to assess the rate and factors predictive of infection. Methods: We performed a retrospective review of patients who underwent EVD placement between January 2012 and January 2018. Results: A total of 714 patients were included in the study. The infection rate was 3.6% (26/714). In 45% of the cases, the indication for ventriculostomy placement was for acute subarachnoid hemorrhage (aSAH) or intracerebral hemorrhage (ICH). Of the factors that were an independently significant predictor of ventriculostomy-associated infection (VAI) was the placement of a second EVD; the likelihood was eight times higher than if only a single EVD was placed (OR: 7.95, 95% CI: 1.01–62.9, p<0.05). Another factor was routine CSF sampling, associated with greater than nine times higher likelihood of VAI compared to no routine CSF sampling (OR: 9.20, 95% CI: 1.93–43.9, p<0.01). Intrathecal (IT) drug deliveries were also associated with a higher likelihood of VAI (OR: 55.7, 95%CI: 2.92- 1060, p<0.01). Non-significant factors were day vs. night, location (ICU/ER vs. OR), duration, CSF leak, suture type, system flushing. Conclusion: Our study shows that the rate of VAI was 3.6%. Only three variables were significant independent predictors of VAI; these were the replacement of the EVD, routine CSF aspiration, and intrathecal drug delivery. Disclosures: A. Sweid: None. S. Tjoumakaris: None. C. Wamsley: None. E. Mann: None. C. Neely: None. J. Head: None. M. Gooch: None. N. Herial: None. T. Alexander: None. S. Missios: None. N. Chalouhi: None. R. Rosenwasser: None. P. Jabbour: None.